The Image Of Japan in the Philippine Periodical La Solidaridad (1889-1895) - Maligaya, Renato G.; Mamaradlo, Maria Luisa A.; Demeterio III, Feorillo A. (Silliman Journal, 2022)
This paper tries to inductively understand how some articles in the Philippine periodical La Solidaridad that directly talked about Japan convey an overall image of this Empire of the Rising Sun. This paper is significant in the sense that this can contribute towards the understanding of how the Filipino intellectuals during the Propaganda Movement thought about the Philippines in relation to its Asian neighbors as well as about the dynamics of power in the Asian region. This project is also significant in the sense that it retrieves a Filipino imagination of Japan prior to the modifications brought about by the Japanese Occupation in the Philippines and the altercations brought about by the Second World War. To achieve such goals, this paper contains four substantive sections that deal with the following: how thearticles talked about the First Sino-Japanese War; how the same articles talked about Japan and the Philippines/Spain; how the same articles talked about Japanese culture and character; and how the same articles talked about some featured Japanese personalities. This paper establishes that the image of Japan in this said periodical is a composite picture consists of the threatened Spanish Empire, the disinterested Austro-Hungarian Empire, and the reformist and assimilationist Filipino intellectuals.